BIM - Implementación de la metodología para la consultoría de empresas constructoras (2020)
The present investigation seeks to know the state of progress for the implementation of the BIM (Bulding information Modeling) methodology within the consulting or construction companies, on an evaluation of a process resulting from a state of the art that feeds on technological advances , work methodology, resource management in consulting, construction, research or training projects. The benefits and limitations of the implementation of the BIM methodology in Project Management from a maturation stage will be identified, for the commercial, technical areas (development of conceptual, basic and detailed engineering), planning (costs and time) and the quality of service. It will also be developed within the construction stage under a management development implementation, this will be a process by which conclusions and recommendations are drawn to be included in the financial models of the companies and thus have the organization on base guidelines according to the BIM methodology with international standards and quality within a project management at project management level.